MORAL DEVELOPMENT OF MUSLIM YOUTH THROUGH SOCIAL MEDIA - Marpuah, Siti; Hassan, Muhammad Najmi; Mohd Khalid, Halimi; Lasmi, L.; Nuraini, N. (Jurnal 'Ulwan, 2025)
The moral development of Muslim youth is significant in realizing the current generation's relationship with the increasingly challenging influence of social media. This study was carried out to identify the use of social media in developing the morals of Muslim Youth. This study is quantitative and is conducted by distributing questionnaires to all 250 respondents. This research is based on a descriptive and inferential survey design. The research data was analyzed using the Statistical Package for Social Science (SPSS) version 25.0 software. The study's results found that the descriptive value for the use of social media N=250, Min 3.51, SD= .544 at a moderate level. There is an item that shows the highest value, which is the item Religious speakers use social media to deliver lectures to the community with a mean value of M=3.96, SD=.844, followed by the item Islamic studies for Muslims is easy to approach with social media with a mean value of M=4.38, SD= .773 and the social media item has a positive effect on the moral formation of youths mean value M=4.14, SD=.895 and is at a high level. The results of the findings above show that social media is also one of the media in forming the character of youths nowadays. Therefore, we should be able to take advantage of social media for positive purposes, especially to shape the morals of youths.